Development of 3D Learning Media Applications on Materials Food Chain Using Augmented Technology Reality - Sabrila, Safa; Raharjo, Kalis Rahmawati; Sa’ada, Putri Maulida Fatihatus; Triastuti, Ayu Siwi; Khotimah, Nuringsih Khusnul (Universitas Pendidikan Indonesia (UPI), 2024)
Augmented Reality is a technology that is currently being developed which can combine the virtual world with the real world. With the existence of Augmented Reality (AR) it can function to help the perception and interaction of its users with the real world. In the world of education not many have used Augmented Reality technology and many still use books as learning media. So that the material obtained by students is only in the form of text and 2D images. Therefore, researchers took the initiative to design a learning media in the form of a Food Chain learning application that displays 3D material and living things. It aims to be an interactive and interesting food chain learning tool for grade 5 elementary school students packaged in an Android-based application. This application was created and developed using the Unity 2021.3.12f1 software. The methodology used in developing this application uses the method developed by Luther, which is a multimedia software development method based on six stages, namely Concept, Design, Material Collecting, Assembly, Testing (Testing), and Distribution (Distribution). The results of developing this application can make it easier for teachers to convey material about the food chain.